Religious Pluralism and State Paternalism in Kazakhstan - Podoprigora, Roman A. (The review of faith & international affairs, 2020)
Kazakhstan's government is proud of the existing model of interfaith relations and uses it for claiming legitimacy at home and shaping the country's image abroad. To compare it with the covenantal pluralism ideal as outlined by W. Christopher Stewart, Chris Seiple, and Dennis R. Hoover, we consider both top-down dimensions (legal regulations of the religious sphere) and bottom-up dimensions (focusing on relational dynamics and interfaith dialogues). We find major discrepancies and argue that state paternalism, in-built hierarchies, and widespread suspicions and prejudices against religious minorities, inherited from the Soviet times, remain key features of the Kazakhstan model.